2013
DOI: 10.1002/ps.3432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the RNA interference effects triggered by dsRNA and siRNA in Triboliumcastaneum

Abstract: SiRNAs were less efficient than their corresponding dsRNAs. Most of them could hardly trigger any phenotypic changes owing to the temporary silencing effect on target genes. Meanwhile, the efficiency of different siRNAs varied with their matching sequence, and careful selection was necessary for proper use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…Injecting the same amount of corresponding siRNA, however, yielded only 45% silencing from days 2-4 with no observable phenotypic changes (Wang et al, 2013). These findings, coupled with the recent observation that clathrin-mediated endocytosis serves as the predominant cellular uptake mechanism for dsRNA in T. castaneum (Xiao et al, 2015), points to possible lengthdependent uptake of dsRNA in T. castaneum as has been observed in S2 cells.…”
Section: Nucleotide Sequence Lengthsupporting
confidence: 59%
“…Injecting the same amount of corresponding siRNA, however, yielded only 45% silencing from days 2-4 with no observable phenotypic changes (Wang et al, 2013). These findings, coupled with the recent observation that clathrin-mediated endocytosis serves as the predominant cellular uptake mechanism for dsRNA in T. castaneum (Xiao et al, 2015), points to possible lengthdependent uptake of dsRNA in T. castaneum as has been observed in S2 cells.…”
Section: Nucleotide Sequence Lengthsupporting
confidence: 59%
“…The thermal cycling conditions were as follows: 40 cycles at 95 °C for 30 s, 58 °C for 30 s, and 72 °C for 45 s and a last extension at 72 °C for 10 min9. Purified TRE amplicons were in-vitro transcribed using T7 RiboMax Express RNAi System (Promega, Madison, USA)71. GFP amplicon was used to prepare control dsRNA.…”
Section: Methodsmentioning
confidence: 99%
“…RNAi has also been employed for the silencing of vital genes in Tribolium castaneum , Nilaparvata lugens and other insects [4, 6]. Furthermore, RNAi could be used in novel methods of pest management and may be more effective than other pest control measures once the problems of the efficiency and specificity of gene silencing are solved [7]. …”
Section: Introductionmentioning
confidence: 99%
“…T. castaneum is a holometabolous insect in the larva, pupa and adult stages and represents a serious pest that damages grain in storage. It is thought to be an effective and reliable insect for conducting RNAi research [7, 31, 32]. It has also been reported that RNAi is highly effective in Tribolium , even in the postembryonic stages of Tribolium [9, 33].…”
Section: Introductionmentioning
confidence: 99%